Modernidade e exclusão social na urbs viciosa: Curitiba, início do século XX (TEL Tempo, Espaço e Linguagem, 2021)
Abstract: This paper’s objective is to analyze chronicles of the newspaper O Paraná, published in the city of Curitiba between 1907 and 1911, to unveil certain modern sensibilities of the period. These sensibilities appeared in the words of the writers, who were aware of the dangers and contradictions of the modern times (such as the spaces of progress and exclusion of the city) but, at the same time, who were seduced by it. Keywords: Modernity; Social Exclusion; Curitiba;